Evidence for the reliability and validity, and some support for the practical utility of the two-factor Consideration of Future Consequences Scale-14. (August 2016) - McKay, Michael T.; Perry, John L.; Percy, Andrew; Cole, Jon C.
Abstract: Researchers have proposed 1-factor, 2-factor, and bifactor solutions to the 12-item Consideration of Future Consequences Scale (CFCS-12). In order to overcome some measurement problems and to create a robust and conceptually useful two-factor scale the CFCS-12 was recently modified to include two new items and to become the CFCS-14. Using a University sample, we tested four competing models for the CFCS-14: (a) a 12-item unidimensional model, (b) a model fitted for two uncorrelated factors (CFC-Immediate and CFC-Future), (c) a model fitted for two correlated factors (CFC-I and CFC-F), and (d) a bifactor model. Results suggested that the addition of the two new items has strengthened the viability of a two factor solution of the CFCS-14. Results of linear regression models suggest that the CFC-F factor is redundant. Further studies using alcohol and mental health indicators are required to test this redundancy. Highlights: We examined a number of factor solutions for the CFCS-14. A two-factor solution provided the best fit. Analyses were performed with alcohol use and mental health indicators. The CFCS-14 is psychometrically valid and reliable. The theoretical and practical utility of the two factors is uncertain.